Effects of using Save me leaflet media and Save me application on knowledge and behavior of early adolescents to prevent unwanted pregnancy - Sirisawat, Marasri; Sakunsin , Apisit; Kaewsripon , Krittiyaporn; Kulgole , Jirapa (Medical Journal of Sakon Nakhon Hospital, 2024)
This quasi-experimental research aimed to compare the knowledge and behavior scores in preventing unwanted pregnancy in early adolescents between the group that received knowledge promotion using Save me leaflet media and the group that received knowledge promotion using Save me application. The sample group was 1-3 secondary school students at Phattha Pittayakhom School, Tha Uthen District, Nakhon Phanom Province, 50 people per group, totaling 100 people. The research instruments were Save me leaflet media and Save me application developed by the researcher. The data collection instruments were the knowledge and behavior assessment form in preventing unwanted pregnancy. Knowledge scores and behavior scores were compared between the groups using the Independent t-test. The results showed that after the experiment, 1) the average knowledge scores in the group that used Save me leaflet media (Mean = 13.45, S.D. = 1.12) and the experimental group that used Save me application (Mean = 13.90, S.D. = 1.35) increased to a high level. From the hypothesis testing with t-test, it was found that the average knowledge score of both groups was not different. 2) The average behavior score in the group using the Save me leaflet media (Mean = 19.36, S.D. = 3.96) increased at a moderate level, while the group using the Save me application (Mean = 26.62, S.D. = 5.02) increased at a high level and was statistically significant at p<0.05. Therefore, using the Save me leaflet media and using the Save me application can promote knowledge in early adolescents to increase at the same level. However, in terms of behavior, using the save me application was able to promote behavior in early adolescents better than using the Save me leaflet media Keywords: Unwanted pregnancy, Knowledge and behavior in preventing unwanted pregnancy, Early adolescents